2021
DOI: 10.2478/jtes-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers' Change Agency in Education for Sustainable Development

Abstract: Previous research shows that teachers are key players in supporting agency in the face of the biggest global challenges of our time, such as climate change and pollution, as teachers educate societies' future decision-makers. The aim of this study was to analyze student teachers' perceptions of change agency and sustainable development. In this qualitative case study, the writings of student teachers (n = 116) were studied in the context of sustainable development education. The data were analyzed using conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
(58 reference statements)
2
14
0
5
Order By: Relevance
“…Separate courses on ESD have been reported to be somewhat inefficient in creating change agency in teachers [2,7,14,15]. For example, [14][15][16][17] call for a more holistic inclusion of sustainability in strategies and curricula of teacher education. Especially [14] addresses the power of making sustainability competency a visible professional goal in the curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Separate courses on ESD have been reported to be somewhat inefficient in creating change agency in teachers [2,7,14,15]. For example, [14][15][16][17] call for a more holistic inclusion of sustainability in strategies and curricula of teacher education. Especially [14] addresses the power of making sustainability competency a visible professional goal in the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The hesitant notions are reflections of teacher students becoming more aware of the "doing and being" potentials of teachers. This is related to becoming aware of how huge and difficult a phenomenon sustainability is [15]. The next step would be to start thinking about how to realize sustainability in their teaching practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of previous research on climate change from the student teachers' perspective point out the fact that student teachers are mostly aware of the sustainable development issues at both the local and national level, while frequently underestimating the importance of global ecological problems such as climate change (Spiropoulou et al 2007). While reflect-ing on sustainable development as well as their role in shifting towards it, student teachers are mostly focused on its social dimension, while neglecting critical global topics as well as their role in coping with issues such as climate change (Koskela and Kärkkäinen 2021). One potential explanation for this situation can be found in the results of IEA International Civic and Citizenship Education Study from 2016 that revealed that percentages of teachers in Croatia reporting having participated in training courses on civic-related topics, namely the environment and environmental sustainability during pre-service and/or in-service training was only 28% (Schulz et al 2018).…”
Section: Introductionmentioning
confidence: 99%